PRELIMINARY MYCOCHEMICAL, GAS CHROMATOGRAPHY–MASS SPECTROSCOPY ANALYSIS, AND ANTIMICROBIAL PROPERTIES OF CALOCERA VISCOSA (PERS.) FR. - NAIK S, NAVEEN KUMAR; R, ASHWATHANARAYANA; NAIKA, RAJA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Calocera viscosa, commonly called as the yellow stagshorn, is a jelly fungus, belongs to the family of Dacrymycetales, unknown for its medicinal properties and biological activities. Method: The sporocarps of C. viscosa (Pers.) Fr. were collected from Agumbe, Karnataka. Mycochemical and Gas chromatography–mass spectroscopy (GC–MS) analysis done by standard procedures and antibacterial activity was done by agar well diffusion method. Results: Physicochemical was analyzed and results revealed the highest percentage of alcohol-soluble extractives were present followed by ash content. Alcohol-soluble extractives were 20.76%, total moisture content (10.9%), and foreign matter (0.5%). Extraction was done by Soxhlet apparatus using petroleum ether, chloroform, and ethanol and subjected to qualitative mycochemicals analysis both petroleum ether and chloroform extract confirms less mycochemicals, whereas ethanolic extract revealed the presence of alkaloids, tannins, flavonoids, sterols, glycosides, terpenoids, and phenols. GC–MS analysis of ethanoic extract showed many known bioactive compounds in that, 19 compounds were unknown and 21 compounds were known for its medicinal properties, most of them were food additives and flavoring agents. Antibacterial potentials were studied against pathogenic bacteria revealed that ethanolic extract showed appreciable zone of inhibition against pathogenic bacteria, in that maximum zone of inhibition showed against Klebsiella pneumonia followed by Escherichia coli and Staphylococcus aureus. Conclusion: C. viscosa (Pers.) Fr. sporocarp can be explored for potential antibacterial with rich full of useful mycochemicals.